EFFECT OF VARIATIONS IN HEATING TEMPERATURE AND COOLING MEDIA ON THE HARDNESS AND MICROSTRUCTURE OF STEEL ST 41 HARDENING METHOD - Hajar Isworo; Najib Rahman (Scientific Journal of Mechanical Engineering Kinematika, 2020)
ST 41 steel is one of the types of low carbon steel group whose mechanical properties can be improved by means of the heat treatment process. Hardening is a heat treatment process that aims to increase the hardness and strength of steel by heating, holding and cooling in certain time intervals and cooling media. The purpose of this study was to determine the effect of heating temperature and cooling media on the hardness and microstructure of ST 41 steel. The hardening process was carried out at austenite temperatures(850oC, 900oC and 950oC) with a holding time of 15 minutes then cooled quickly using a cooling medium of distilled water, SAE oil 20W-50, and coconut water. The test results show the optimum hardness value is 326.2 HV at 850oC heating temperature with water cooling media and a minimum hardness of 153.1 HV at 950oC heating temperature with SAE 20W-50 oil cooling media, while theresults of microstructure testing after the hardening process show that the structure formed are martensite and bainite. From this study it can be concluded that the hardening process can increase the value of hardness in ST 41 steel.